Japanese Direct Investment in Mexico's Transport Equipment Sector Macro Impact and Local Responses (New Frontiers in Regional Science: Asian Perspectives,, 2018)
This book introduces an interdisciplinary approach to the study of Japanese foreign direct investment determinants, the close relations between foreign investment and trade flows in the host country, and the effects and responses by the local economy. It provides an accessible and comprehensive view of the overall macro impacts and local effects associated with the increasing flow of Japanese firms to Mexico's automotive industry. The research and its outcomes presented here follow extensive fieldwork and use unique statistical datasets to integrate qualitative and quantitative approaches to the analysis. Carefully chosen case studies produce an integrated approach to the subject. As a result, the book fills a vacuum on this topic and provides readers with a clear understanding of the complex interactions among participating actors: Japanese multinationals and Japanese parts-and-components suppliers, Mexican local suppliers, government at the national and local levels, and cooperating Japanese agencies. By critically assessing current theories and empirical methodologies the monograph covers aspects related to the creation of regional production networks and their impact on trade patterns of the recipient country, location determinants of Japanese foreign investment, and spillover externalities in host entities. It presents the reader with a comprehensive view of the different levels of interaction between multinational firms, local recipient economies, and local suppliers and the challenges they face to engage in global chains of production. The book is highly recommended to academics and their students who seek to understand the complex international economic relations in the global economy. This compilation also serves as a valuable guide to policy makers, both at national and local levels, as it provides an informed analysis of how to engage local suppliers in regional and global production chains.